Importance and Scope of Implementing Project Based Learning in Tier-II Engineering Colleges - Kurapati, Anusha; Syed, Khamruddin (Journal of Engineering Education Transformations, 2017)
Project Based Learning (PBL) is a one of the important teaching methods in which student's gain knowledge and skills by working together for an extended period of time to investigate and respond to an authentic, engaging and complex question, problem, or challenge. In Tier-II engineering colleges, it is difficult to implement PBL because of rigid curriculum developed by affiliated university. Many papers focused on the importance of PBL and how they succeed, but could not address how to implement in Tier-II colleges. To address this problem, in K. G. Reddy College of Engineering&Technology, we have started implementing a few techniques. This paper gives some thoughts related to PBL in those colleges. The grading criteria of the students in Tier-II colleges will be evaluated based on their performance in the project. This method will likely impact the Engineering Education in the future.